2019
DOI: 10.1002/ejoc.201900082
|View full text |Cite
|
Sign up to set email alerts
|

Croconaine Rotaxane Dye with 984 nm Absorption: Wavelength‐Selective Photothermal Heating

Abstract: Croconaines are an emerging class of near‐infrared dyes that are useful for various sensing, photothermal, optoelectronic, and photoacoustic applications. Previous work encapsulated a dumbbell‐shaped croconaine dye whose structure contains two thiophene flanking units inside a tetralactam macrocycle and produced a croconaine rotaxane 1 with a narrow 824 nm absorption band. Herein, a new rotaxane 2 is reported that encapsulates a croconaine dye with two thienothiophene flanking units. The new croconaine rotaxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…So far, most of the reported croconaines have absorption peaks in the NIR-I region . Although their absorption can be tuned by introducing large planar donors, this strategy remains difficult to push the absorption to the NIR-II range. It is also reported that croconic acid reacts with phenolic hydroxyl groups on both sides after ring opening occurs, obtaining an NIR-II-absorbing isomerized product, but its yield and molar absorption coefficient are both very low.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the reported croconaines have absorption peaks in the NIR-I region . Although their absorption can be tuned by introducing large planar donors, this strategy remains difficult to push the absorption to the NIR-II range. It is also reported that croconic acid reacts with phenolic hydroxyl groups on both sides after ring opening occurs, obtaining an NIR-II-absorbing isomerized product, but its yield and molar absorption coefficient are both very low.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes and pigments featuring rotaxane topologies are known in the scientific community and find application as nanoscale switches in molecular electronics amongst others. [ 1 , 2 , 3 , 4 , 5 ] In this work, we investigate a supramolecular photovoltaics approach to rectify charge propagation in solar cells through the use of rotaxane sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of metabolic state in tumor tissue results in peculiar extracellular chemical composition, which leads to the TME being slightly more acidic (pH 6.5–7.0) than normal tissues . The absorption of some NIR organic dyes could be readily tuned in the acidic environment, thus proving to be potentially pH-sensitive PA contrast agents. Recently, pH-sensitive Croc dyes exhibited strong NIR absorption and intense photothermal conversion efficiency with remarkable chemical and thermal stability, making them a promising agent for PA as well as PTT. However, their poor solubility in aqueous solution hinders in vivo biomedical use . There are reports on chemical modification of Croc dyes to improve their biocompatibility through self-assembled HSA-Croc NPs and PEGylation of CR780 (a Croc dye) NPs for PA imaging and PTT. , …”
Section: Introductionmentioning
confidence: 99%